2021
DOI: 10.1016/j.ajic.2020.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Minimizing contamination in the use of personal protective equipment: Simulation results through tracking contamination and enhanced protocols

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 13 publications
0
12
0
Order By: Relevance
“…One simple but effective measure, with demonstrable effectiveness, is to provide HCWs with a full‐length dressing mirror so they can observe their actions when donning and doffing PPE (Xia et al, 2020 ). Only a minority of respondents were highly confident of the protection provided from PPE and simulation‐based training might also alleviate HCWs' fear of being contaminated and instil them with more confidence that PPE use provides them with sufficient protection from airborne pathogens such as the COVID‐19 virus (Kang et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…One simple but effective measure, with demonstrable effectiveness, is to provide HCWs with a full‐length dressing mirror so they can observe their actions when donning and doffing PPE (Xia et al, 2020 ). Only a minority of respondents were highly confident of the protection provided from PPE and simulation‐based training might also alleviate HCWs' fear of being contaminated and instil them with more confidence that PPE use provides them with sufficient protection from airborne pathogens such as the COVID‐19 virus (Kang et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…HCWs reported heat, thirst, areas of pressure, headache, difficulty going to the bathroom, severe exhaustion. Researchers confirmed the need for regular PPE training to avoid carelessness or forgetfulness of the trained HCW in the details of PPE use (Kang et al, 2021). Other commonly reported problems with the use of PPE were difficulty breathing, suffocation, heat stress and cloudy glass (Chughtai et al, 2018).…”
Section: Personal Protective Equipment (Ppe) and Health Care Workers (Hcw)mentioning
confidence: 90%
“…In addition to having PPE in the necessary amount, the correct use and disposal have an impact on protection. It is also important to have an adequate process for doffing (removal) and disposing of contaminated PPE (Chughtai et al, 2018;Kang et al, 2021).…”
Section: Personal Protective Equipment (Ppe) and Health Care Workers (Hcw)mentioning
confidence: 99%
“…6,23 Pre-doffing location of tracer contamination varied among the studies of enhanced PPE ensembles (Table 1): Six studies placed the tracer at extensive locations across the body, while three studies placed the tracer at a few locations, and two studies placed tracer to the environment and noted pre-doffing contamination. 23,28 Studies using fluorescent tracer assessed post-doffing contamination on the entire body, or nearly the entire body, while other tracers were typically assessed more selectively. Kwon et al 14 for example, swabbed areas showing fluorescent contamination for MS2, and Andonian et al 6 swabbed the hands, wrists, face, and ears for PSLs.…”
Section: Enhanced Ppe Ensemblesmentioning
confidence: 99%
“…Potential determinants of post doffing contamination were explored in seven studies. 7,14,16,20,23,28 Three studies attributed contamination to deviation from doffing protocol. 7,14,23 One study attributed observed neck contamination to pre-doffing application of tracer.…”
Section: Enhanced Ppe Ensemblesmentioning
confidence: 99%